Evaluación técnica del uso del carbonato de calcio en las propiedades reológicas de un fluido de perforación para un campo del Norte de Santander (2020)
By implementing silos as a storage medium for calcium carbonate a successful operation will be carried out more easily, because it It retains the quality of the input. The technical comparison of calcium carbonate currently employed with Calcium Carbonate extracted from the mine of Santander will allow an economic analysis, facilities and implementation in the Field, verifying that the ore extracted from said mine complies with the standard conditions stipulated by Colombian regulations, likewise prove that the quality is equal to or even superior to that of the calcium carbonate used currently in the field.